Chemical Composition and Potential Biological Activity of Melanoidins From Instant Soluble Coffee and Instant Soluble Barley: A Comparative Study - Antonietti, Sofia; Silva, Amélia M.; Simões, Cristiana; Almeida, Diana; Félix, Luis M.; Papetti, Adele; Nunes, Fernando M. (Frontiers in Nutrition, 2022)
In this work a comparative study of the chemical composition and potential biological activity of high molecular weight (HMW) melanoidins isolated from instant soluble coffee (ISC) and instant soluble barley (ISB) was performed. ISB HMW melanoidins were almost exclusively composed by an ethanol soluble (EtSn) melanoidin fraction composed by glucose (76% w/w) partially susceptible to in vitro digestion, whereas ISC was composed mainly by arabinogalactans (~41% w/w) and lower amounts of galactomannans (~14% w/w) presenting a range of ethanol solubilities and resistant to in vitro digestion. Melanoidins from ISC presented a significantly higher content of condensed phenolic compounds (92 mmol/100g) when compared to ISB (46 mmol/100g) showing also a higher in vitro scavenging of ABTS•+ (329 mmol Trolox/100g vs 124 mmol Trolox/100g) and NO radicals (inhibition percentage of 57 and 26%, respectively). Nevertheless, ISB EtSn melanoidins presented, on average a higher inhibitory effect on NO production from LPS-stimulated macrophages. ISB melanoidins, up to 1 mg/mL, did not induce toxicity in Caco-2, HepG2 and RAW 264.7 cell lines while at the highest concentration ISC slightly reduced cell viability. Thus, consumption of a diet rich in ISC and ISB melanoidins may reduce the oxidative stress of nitric oxide and increase the protective effects against cardiovascular and chronic inflammatory diseases.